El cine / cuento animado o la ruptura del modelo clásico - Sánchez Moreno, Ana Belén (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2009)
The wonderful world of the classic tale, which inspired the animations films for decades, has given way to different topics and characters. Thus, it has been opened a potential of new ideas favoured in many cases by the digital creation and 3D-Technology. For years, the monopoly of Disney Company was clear, offering through its full-length films a vision of the world full of values that reached to the public of different ages. Disney surrended to the new technologies of the picture, and other companies like Dreamworks started to compete against it through new, imaginative proposals. The Videogame world, Internet or the Mass Media have opened a window to the world which implies the necessity of “watching” anf “feeling” in a different way, compelling to make more and more necessary a solid audiovisual culture. All this causes changes in the audience, especially in the children´s, which is moving along the new values and contents also introduced in the animation universe.